THE APPLICATION OF AGRIBUSINESS FISHERIES SYSTEM ON UNIT PEMBENIHAN RAKYAT (UPR) IN REGENCY SIMALUNGUN NORTH SUMATRA PROVINCE - Siahaan, Monalia Triwati; Hamid, Hamdi; ', Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on December 9 -19 December 2015, in the Unit Pembenihan Rakyat (UPR), which took place in the Simalungun’s District. The purpose of this study was to see the implementation of agribusiness system in the UPR and analyze the UPR business simple. The method used in this study was a survey method which analyze primary data that have been obtained in the field. Determining respondents taken by purposive sampling.Based on research that has been conducted in the UPR, the result that the number of UPR of the 2010-2014 decline. This is due to the population still focused on agriculture and do a hatchery operations as a sideline. However, UPR is still running has increased quite good. Improvements have been achieved in the form of an increased extent, the amount of production is increasing every year as well as the volume of marketing that continues to grow. However, the UPR still face difficulties in business operations. The problems experienced by the UPR are buyer didn’t do payment at same time when they buy seeds, life insurance seeds get longer, forming a group that just to get government assistance and financial administration not to get structured.Keywords: System, Agribusiness, UPR